Diagnostic Dilemma due to Atypical Presentation of Sublingual Thyroid Ectopia: A Case Report (Bangladesh Journal of Nuclear Medicine, 2023)
Thyroid tissue may be found in an abnormal location along the thyroglossal duct tract or other sites due to abnormal embryologic development and migration. Thyroid ectopia is an uncommon but well-documented clinical entity. In the event of any neck swelling, it should be kept as a differential diagnosis. Thyroid scintigraphy plays a very important role in diagnosing ectopic thyroid, with the complementary primary role of high-resolution neck ultrasonography (HRUS). Reported case of an 18-year-old male referred to INMAS for evaluation of a slowly enlarging submental swelling with no history of dysphagia or dyspnea was biochemically hypothyroid. Patient had a history of submental swelling that was misdiagnosed as an abscess, creating a diagnostic dilemma, as he was found to have glandular tuberculosis after surgical drainage of the lesion.Bangladesh J. Nuclear Med. 25(2): 125-127, 2022